Last before-death transmission in patients with heart failure and implantable cardioverter-defibrillator followed by remote monitoring - insights from the COMMIT-HF registry. (24th May 2021) - Dyrbus, M; Tajstra, M; Pyka, L; Kurek, A; Gasior, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background Remote monitoring (RM) of cardiac implantable electronic devices (CIED) in patients with heart failure allows to regularly analyze the devices" and patients" conditions. Purpose The purpose of this study was evaluation of the ultimate transmissions sent before death in patients monitored remotely. Methods The last transmissions delivered by the devices in patients enrolled into COMMIT-HF Registry (NCT02536443) who died when monitored remotely have been retrospectively analysed. The characteristics and contents of the transmissions and clinical reactions undertaken have been obtained from the RM systems of four major RM providers. Results Of 1, 306 patients with CIEDs who were enrolled at the RM programme in our centre, 267 died and their last transmission occurred less than 90 days before death, of which 133 (49.8%) were scheduled and 134 (50.2%) alert-triggered. The median period between transmission and death was 31 days for scheduled and 8 days for alert-triggered transmissions. The most frequent alert-triggered transmissions were atrial fibrillation/flutter (35.8%) and ventricular tachyarrhythmias (24.6%). A clinical reaction has been undertaken after 9.8% of planned and 67.1% of alert-triggered transmissions and consisted mainly of telephone consultations and referrals for hospital admissions. Conclusions This is the first analysis of the ultimate transmissions delivered by CIEDs before death. In approximately 50% of patients, the last transmission has been alert-triggered. Hence, an appropriate organization of the RM facility, which should immediately analyse and react to the transmission, seems mandatory to obtain clinical benefit in patients with HF and RM.